Gender differences in oesophageal mucosal injury in a reflux oesophagitis model of rats. Issue 1 (27th January 2012) - Masaka, Tomohiro; Iijima, Katsunori; Endo, Hiroyuki; Asanuma, Kiyotaka; Ara, Nobuyuki; Ishiyama, Fumitake; Asano, Naoki; Koike, Tomoyuki; Imatani, Akira; Shimosegawa, Tooru
Abstract : Objective: There is a strong male predominance of oesophageal adenocarcinoma, which might be related to the higher prevalence of precursor lesions such as erosive reflux oesophagitis in men compared with women. This experiment investigated the gender difference in a reflux oesophagitis model of rats and explored the potential role of oestrogen in controlling oesophageal tissue damage. Design: An acid-reflux oesophagitis model was surgically produced in male and female rats, and ascorbic acid in the diet and sodium nitrite in the drinking water were administered to half of either group to provoke luminal exogenous nitric oxide (NO) as an exacerbating agent. Seven days after the surgery, the oesophagus was excised, and the injury area, myeloperoxidase activity and pro-inflammatory cytokine levels were measured. Furthermore, 17β-oestradiol was administered to ovariectomised female rats or male rats, which then underwent reflux oesophagitis surgery. Results: While there was no gender difference in oesophageal damage in the baseline model, oesophageal damage was more intensively observed in males than in females in the presence of exogenous NO administration. While oesophageal damage was increased in ovariectomised rats compared with sham ovariectomised, exacerbated oesophageal damage was attenuated by the replacement of 17β-oestradiol. In addition, exacerbated oesophageal damage in male rats was suppressed by 17β-oestradiol. Conclusion: This is the first study showing the prominent gender difference in the severity of oesophageal tissue damage in a gastro-oesophageal reflux disease-related animal model, highlighting the critical involvement of oestrogen in controlling gastro-oesophageal reflux disease-related oesophageal epithelial injury.